Complex I and MDM2: hit me baby one more time. (4th July 2019) - Chipuk, Jerry Edward
ABSTRACT: MDM2 (mouse double minute 2) functions as both a tumor suppressor and oncogene, yet little is known if MDM2 regulates cancer cell biology by altering cellular metabolism. We recently found that MDM2 binds NDUFS1 (NADH:ubiquinone oxidoreductase 75 kDa Fe-S protein 1), a key protein involved in Complex I assembly, function, and efficiency. The MDM2⋅NDUFS1 interaction promotes reactive oxygen species production, DNA damage, and apoptosis.